2022
DOI: 10.3389/fpls.2022.853546
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation on the Yield, Quality, and Water-Nitrogen Use Efficiency of Mountain Apple Under Surge-Root Irrigation in the Loess Plateau Based on the Improved TOPSIS Method

Abstract: The purpose of this study was to know the controlling effects of water and nitrogen coupling on the yield, quality, and water-nitrogen utilization effectiveness of mountain apples under surge-root irrigation in the Loess Plateau. In order to optimize the water and nitrogen irrigation systems of superior quality and high yield, 7 years was selected for the mountain apple test material. The trial was designed with four tiers of irrigation, i.e., full irrigation (FI: 85–100% θf, where θf is the field capacity), l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…On the 20th day of storage, for irrigation treatments, the titratable acid content of W0 treatment was significantly higher than that of other treatments ( P < 0.01), and the titratable acid content of N0 treatment was significantly higher than that of other nitrogen application treatments ( P < 0.01). Our results found that the soluble solids content increased with an increase in the irrigation volume, while the opposite development was discovered for the titratable acid content, which is consistent with observations from previous research studies. ,, For nitrogen application treatments on the 60th day, the titratable acid content of the N0 treatment was significantly lower than that of N1 and N3 treatments ( P < 0.01). The effects of nitrogen application treatment was similar to that of irrigation treatment.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…On the 20th day of storage, for irrigation treatments, the titratable acid content of W0 treatment was significantly higher than that of other treatments ( P < 0.01), and the titratable acid content of N0 treatment was significantly higher than that of other nitrogen application treatments ( P < 0.01). Our results found that the soluble solids content increased with an increase in the irrigation volume, while the opposite development was discovered for the titratable acid content, which is consistent with observations from previous research studies. ,, For nitrogen application treatments on the 60th day, the titratable acid content of the N0 treatment was significantly lower than that of N1 and N3 treatments ( P < 0.01). The effects of nitrogen application treatment was similar to that of irrigation treatment.…”
Section: Resultssupporting
confidence: 91%
“…As the irrigation volume decreased, the hardness of the “Hanfu” apple increased. That is because an insufficient irrigation volume limits the expansion and division of pulp cells, which causes the increase in apple hardness. , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations